AB0735 SEVERITY OF NAIL PSORIASIS SCORE (SNAPS) DEMONSTRATES LONGITUDINAL CONSTRUCT VALIDITY AGAINST THE MODIFIED NAIL PSORIASIS SEVERITY INDEX (mNAPSI) IN AN OBSERVATIONAL COHORT OF PATIENTS WITH PSORIATIC ARTHRITIS. (2nd June 2020) - Antony, A.; Saeed, S.; Hart, D.; Nair, P.; Cavill, C.; Korendowych, E.; Mchugh, N.; Lovell, C.; Tillett, W.
Abstract : Background: Longitudinal observational data on psoriatic nail dystrophy is scarce, in part due to the lack of a validated outcome measure that is feasible in routine care. The Severity of Nail Psoriasis Score (SNAPS; range 0-40: scored one point each for the presence of pitting, onycholysis, hyperkeratosis and/or severe nail disease # in each fingernail) has face validity and has recently demonstrated feasibility, reliability and cross-sectional construct validity against the modified Nail Psoriasis Severity Index (mNAPSI; range 0-130) 1 . Objectives: We aimed to assess the longitudinal construct validity of SNAPS against the mNAPSI and physician nail VAS (PhNVAS), and to determine the effect size and measurement error of these tools. Methods: Consenting consecutive patients enrolled in the Bath Psoriatic Arthritis (PsA) longitudinal cohort underwent photography of their fingernails at baseline 1 and 6 months alongside routine clinical assessments. Dorsal images of individual fingernails were acquired using a tripod mounted DSLR camera. An angled mirror positioned distally aided identification of hyperkeratosis. Photograps were scored using SNAPS, mNAPSI and PhNVAS 1 . Paired statistical analyses were conducted to assess for change in scores from baseline to follow-up. Pairwise correlations between change in SNAPS and change in mNAPSI and PhyNVAS were assessed using Spearman's rho. Effect sizes and measurement error were calculated. Results: Fifteen patients with a mean (±SD) age of 54.5 (±10.59) were assessed at 6 months. There was a significant reduction in both the mNAPSI and SNAPS scores (p<0.005), with improvements in the most frequently-observed manifestations 1 i.e. pitting, onycholysis, hyperkeratosis and crumbling (Table 1). No other feature specific to mNAPSI improved over time. There was no significant change using the PhyNVAS. There was a strong correlation between changes in SNAPS and the mNAPSI (Figure 1; rho = 0.838, p<0.001). The correlation between change in SNAPS and PhyNVAS was not statistically significant (rho =0.45, p=0.095) (Figure 1). The change in mNAPSI correlated moderately with the PhNVAS (rho = 0.540, p=0.038). mNAPSI was superior to SNAPS in most parameters of measurement error (Table 2). The mNAPSI and SNAPS had similar effect sizes as measured by the SRM (Table 2). Conclusion: SNAPS demonstrates longitudinal construct validity against the mNAPSI in a small observational cohort of PsA patients as evidenced by a strong correlation between the measures, comparable effect sizes and sensitivity to change over time. Whilst measurement error parameters favored the mNAPSI, SNAPS may be a more feasible measure for studying nail disease in cohort studies. References: [1]Antony A, Hart D, Cavill C, Korendowych E, McHugh N, Lovell C, Tillett W. The 'Severity of Nail Psoriasis Score' (SNAPS) Is Feasible, Reliable and Demonstrates Construct Validity Against the mNAPSI in an Observational Cohort of Patients with Psoriatic Arthritis [abstract]. Arthritis Rheumatol. 2019; 71 (suppl 10). Disclosure of Interests: Anna Antony: None declared, Sadaf Saeed: None declared, Darren Hart: None declared, Preeti Nair: None declared, Charlotte Cavill: None declared, Eleanor Korendowych: None declared, Neil McHugh: None declared, Christopher Lovell: None declared, William Tillett Grant/research support from: AbbVie, Celgene, Eli Lilly, Janssen, Novartis, Pfizer Inc, UCB, Consultant of: AbbVie, Amgen, Celgene, Lilly, Janssen, Novartis, MSD, Pfizer Inc, UCB, Speakers bureau: AbbVie, Amgen, Celgene, Lilly, Janssen, Novartis, Pfizer Inc, UCB